Combination of Forestier’s disease and laryngeal cancer: a rare clinical case - А. М. Zaytsev; А. P. Polyakov; М. V. Ratushny; Т. М. Kobyletskaya; S. А. Kisariev; А. L. Sugaipov; О. N. Kirsanova (Опухоли головы и шеи, 2020)
The objective of the scientific report is to describe a rare clinical case of a combination of Forestier’s disease (diffuse idiopathic skeletal hyperostosis) and laryngeal cancer that have common symptoms. Case report. A 68-year-old male patient presented with hoarseness lasting for a year. Indirect laryngoscopy revealed a vocal fold tumor. Histological examination confirmed well-differentiated keratinizing squamous cell carcinoma of the larynx. A 6-cm tumor was located in the projection of the right vocal fold and had no signs of invasion into the supraglottis, subglottis, and anterior commissure. No other focal disorders were detected. The patient has undergone endolaryngeal laser resection of the larynx and tracheostomy. After probe removal, the patient had swallowing difficulties with esophageal content passing to the trachea mainly due to organic changes in the cervical spine at the СЗ–С4 level, where there was a massive local calcification of the anterior longitudinal ligament. We also noticed severe movement restriction in the cervical spine: the amplitude of movements did not exceed 10°. The formation of the C3–C4 segment was removed via ventrolateral approach. Conclusion. Dysphagia, dysphonia, and dyspnea may indicate both malignant tumor and large osteophyte causing compression of the trachea and esophagus. In this case, no symptom resolution after tumor removal led to the suspicion of a second disease, namely Forestier’s disease.